Postoperative Admission of Adult Craniotomy Patients to the Neuroscience Ward Reduces Length of Stay and Cost. Issue 1 (16th April 2021) - Sun, Matthew Z; Babayan, Diana; Chen, Jia-Shu; Wang, Maxwell M; Naik, Priyanka K; Reitz, Kara; Li, Jingyi Jessica; Pouratian, Nader; Kim, Won
Abstract: BACKGROUND: The neurointensive care unit (NICU) has traditionally been the default recovery unit after elective craniotomies. OBJECTIVE: To assess whether admitting adult patients without significant comorbidities to the neuroscience ward (NW) instead of NICU for recovery resulted in similar clinical outcome while reducing length of stay (LOS) and hospitalization cost. METHODS: We retrospectively analyzed the clinical and cost data of adult patients undergoing supratentorial craniotomy at a university hospital within a 5-yr period who had a LOS less than 7 d. We compared those admitted to the NICU for 1 night of recovery versus those directly admitted to the NW. RESULTS: The NICU and NW groups included 340 and 209 patients, respectively, and were comparable in terms of age, ethnicity, overall health, and expected LOS. NW admissions had shorter LOS (3.046 vs 3.586 d, P < .001), and independently predicted shorter LOS in multivariate analysis. While the NICU group had longer surgeries (6.8 vs 6.4 h), there was no statistically significant difference in the cost of surgery. The NW group was associated with reduced hospitalization cost by 3193 per admission on average ( P < .001). Clinically, there were no statistically significant differences in the rate of return to Operating Room, Emergency Department readmission, or hospital readmission within 30 d. CONCLUSION: Admitting adult craniotomy patients without significant comorbidities, who are expected to have short LOS, to NW was associated with reduced LOS and total cost of admission, without significant differences in postoperative clinical outcome. Graphical Abstract: